A descriptive-contrastive analysis of English and Tagalog proverbs - Segui, Luz (Dawang) 1932-
The purpose of the study is to present a descriptive-contrastive analysis of English and Tagalog proverbs. It attempts to give a scientific description of selected Tagalog proverbs including their moral values, and their implications to the economic, social, emotional and religious life of the people.